REVIEWS. Issue 3 (10th July 2012) - Anton, Corey; Dress, Abby
KORZYBSKI: A BIOGRAPHY, BY BRUCE I. KODISH, (2011) Pasadena CA: Extensional Publishing, (694 pp.) ISBN 978-0970066404 29.95 (paperback)FAST MEDIA, MEDIA FAST: HOW TO CLEAR YOUR MIND AND INVIGORATE YOUR LIFE IN AN AGE OF MEDIA OVERLOAD, BY THOMAS W. COOPER, (2011) Boulder, CO: Gaeta Press, (225 pp.) ISBN: 978-1-4520-8500-5, 19.95 (paperback)